Chimeric antigen receptor T cell treatment in hematologic malignancies. Issue 1 (February 2016) - Goker, Hakan; Malkan, Umit Yavuz; Demiroglu, Haluk; Buyukasik, Yahya
Abstract: Adoptive transfer of T cells that have genetically engineered chimeric antigen receptors (CARs) is an encouraging treatment modality in the hematological malignancies. These T cells are capable of selectively recognizing tumor-associated antigens. There are a variety of reported, as well as ongoing studies on the utilization of CAR-T cells in the treatment of leukemia, myeloma, as well as B and T cell lymphomas. In this review, we aimed to highlight current understanding of this promising treatment modality, including its efficacy and adverse effects.